Liu-Type Logistic Estimator - EYGİ ERDOĞAN, BİRSEN; İNAN, DENİZ (TAYLOR & FRANCIS INC, 2013)
It is known that multicollinearity inflates the variance of the maximum likelihood estimator in logistic regression. Especially, if the primary interest is in the coefficients, the impact of collinearity can be very serious. To deal with collinearity, a ridge estimator was proposed by Schaefer et al. The primary interest of this article is to introduce a Liu-type estimator that had a smaller total mean squared error (MSE) than the Schaefer's ridge estimator under certain conditions. Simulation studies were conducted that evaluated the performance of this estimator. Furthermore, the proposed estimator was applied to a real-life dataset.
Keywords: Liu-type estimator; Logistic regression; Multicollinearity; Ridge estimator